Radiation Risk Perception of the Residents Who Provided Land for the Interim Storage Facilities in Okuma and Futaba Towns Adjacent to the Fukushima Daiichi Nuclear Power Plant - Matsunaga, Hitomi; Zabirova, Aizhan; Kashiwazaki, Yuya; Orita, Makiko; Takamura, Noboru (Applied sciences, 2025)
To reduce environmental contamination following the release of various radionuclides during the Fukushima Daiichi Nuclear Power Plant accident, the Japanese government has continued decontamination work and decided to use interim storage facilities (ISFs) in the towns of Okuma and Futaba to house large quantities of contaminated soil and waste until their final disposal. This study aims to clarify whether there are differences in the acceptance of removed soil for recycling between people who provided land for ISFs and those who do not. Furthermore, we analyzed the risk perception of the radiation effects on offspring, trust in information from public authorities, and intention to return to their hometown. A questionnaire survey was conducted at Okuma and Futaba town homes in the ISF area. Compared with those who did not provide land to the ISFs (n = 538, 68.0%), people who provided land (n = 141, 77.9%) responded that they were accepting the building of the ISFs (p = 0.018). Meanwhile, approximately half of the respondents were “unable to decide” concerning the recycling of removed soil in their current region of residence regardless of whether the land provided or not. Similarly, there were no significant differences between the groups regarding radiation risk perceptions of the offspring effects on residents and intention to return, or whether to provide land to the ISFs. The study suggests that it is important to continue radiation risk communication to determine whether people have provided land to the ISFs.